Penerapan Metode Role Playing dengan Pendekatan Culturally Responsive Teaching untuk Meningkatkan Keterampilan Berbicara Siswa Kelas V - Anita Rahma Hardiyanti; Pinkan Amita Tri Prasasti; Ritha Hima Watie (Journal Innovation In Education, 2024)
This research uses the application of the Role Playing Method with a Culturally Responsive Teaching Approach to Improve the Speaking Skills of Class V Students. This research is classroom action research with two cycles. Both cycles include planning, action implementation, observation and reflection stages. The research took 16 fifth grade elementary school students as subjects. Data collection was carried out through observation and descriptive statistical analysis. The research results showed that in cycle I, the average student score was 62.81, which then increased to 80.62 in cycle II. There was also a significant increase in learning completion in the speaking skills of class V students at SDN Munggut 03. In cycle I, there were 3 students (18.75%) who achieved learning completeness, while in cycle II, 11 students (68.75% ) achieving complete learning, and achieving classical learning completeness. The percentage increase from cycle I to cycle II was found to be 17.81%. So, there is an increase shown based on the percentage of speaking skills of class V students. It can be concluded that the application of the Role Playing learning method with a Culturally Responsive Teaching approach can improve the speaking skills of class V students.